Efforts to Increase Learning Activity in History Subjects According to the Learning Styles of Class X-2 Students at SMA Negeri 3 Medan - Hayaturrahmi, Hayaturrahmi; Nugraha, Muhammad Adika; Sihotang, Masniar (ALACRITY : Journal of Education, 2024)
This research was conducted because the learning activity of students in class X-2 of SMA Negeri 3 Medan in history subjects was very low. The aim of this research is to increase students' active efforts in learning history. This research was conducted in the odd semester of the 2024/2025 academic year. This research uses the Kemmis and Taggart model. Data collection techniques through student observation and questionnaires. The data processing technique in this research uses descriptive analysis with percentages. The indicators assessed in this research are problem solving, expressing opinions, cooperation and social relations, and discipline. The results of this research show an increase in student learning activity in class X-2 from pre-cycle, cycle I and a very good improvement in cycle II.